2018
DOI: 10.1097/md.0000000000011963
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the CYR61 gene in patients with acute myeloid leukemia in a Han Chinese population

Abstract: It was demonstrated in previous studies that cysteine-rich angiogenic inducer 61 (Cyr61) plays vital roles in hematological disorders, and we have already reported that the Cyr61 protein is a tumor promoter in acute myeloid leukemia (AML). Here, we investigated the association between CYR61 gene polymorphisms and susceptibility to AML.We genotyped 2 single-nucleotide polymorphisms (rs2297141 and rs6576776) in the region of the CYR61 gene by improved multiplex ligase detection reaction genotyping assays in a to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The polymorphism rs3753794 of the CCN1 gene was shown to be associated with plasma high-density lipoprotein–cholesterol levels in obese individuals [ 13 ]. Chang-Chun Niu et al findings indicated that rs6576776 in the CCN1 gene may be considered potential acute myeloid leukemia risk factors in the Han Chinese population [ 14 ]. So far, the function of rs954353 has not been studied at the cellular and animal levels.…”
Section: Introductionmentioning
confidence: 99%
“…The polymorphism rs3753794 of the CCN1 gene was shown to be associated with plasma high-density lipoprotein–cholesterol levels in obese individuals [ 13 ]. Chang-Chun Niu et al findings indicated that rs6576776 in the CCN1 gene may be considered potential acute myeloid leukemia risk factors in the Han Chinese population [ 14 ]. So far, the function of rs954353 has not been studied at the cellular and animal levels.…”
Section: Introductionmentioning
confidence: 99%
“…AML is associated with favorable, intermediate, and unfavorable risks as per the national comprehensive cancer networks (Xu et al, 2017). Genomic changes play a vital role in AML (Niu et al, 2018). The recent world health organisation (WHO) classifications defines AML with biallelic mutations of CEBPA is recognized as distinct category with favorable prognosis (Ng et al, 2017).…”
Section: Introductionmentioning
confidence: 99%